Apolipoprotein E gene polymorphism, trauma burden, and posttraumatic stress symptoms in U.S. military veterans: Results from the National Health and Resilience in Veterans Study. Issue 2 (24th November 2017) - Mota, Natalie P.; Han, Shizhong; Harpaz‐Rotem, Ilan; Maruff, Paul; Krystal, John H.; Southwick, Steven M.; Gelernter, Joel; Pietrzak, Robert H.
Abstract: Background: Previous research examining the association between apolipoprotein E ( APOE ) gene polymorphism and risk for posttraumatic stress disorder (PTSD) has been inconsistent due to the use of small and select samples. This study examined the relation between APOE genotype and PTSD symptoms in two nationally representative samples of U.S. military veterans. The potential effect of cumulative trauma burden and social support in moderating this association was also evaluated. Methods: The main sample consisted of 1, 386 trauma‐exposed European American (EA) veterans (mean age: 62–63 years) who participated in the National Health and Resilience in Veterans Study (NHRVS) in 2011. The independent replication sample consisted of 509 trauma‐exposed EA veterans from the 2013 NHRVS. Results: APOE ε4 allele carriers reported significantly greater severity of PTSD symptoms than noncarriers in the main, but not the replication, sample. In both samples, the interaction of APOE ε4 carrier status and cumulative trauma burden was associated with greater severity of PTSD symptoms ( F range = 2.53–8.09, all P 's < .01), particularly re‐experiencing/intrusion symptoms ( F range = 3.59–4.24, P 's < .001). Greater social support was associated with lower severity of PTSD symptoms among APOE ε4 allele carriers with greater cumulative trauma burden (β range −.27 to −.60, P 's < .05). Conclusion: U.S. military veterans who are APOE ε4 allele carriers and exposed to a high number of traumas may be at increased risk for developing PTSD symptoms than ε4 noncarriers. Greater social support may moderate this association, thereby highlighting the potential importance of social support promoting interventions in mitigating the effect of ε4 × cumulative trauma burden on PTSD risk.